"Proteger os pretos": havia uma mentalidade reformista na administração portuguesa na África tropical (1926-1961)? - Keese, Alexander (Africana Studia, 2020)
The article represents an attempt to differentiate our víew of Portuguese colonial administration attitudes. After the shocking experience of misery in the Portuguese African provinces, due to the program of economic over-exploitation during the war years, the offícials' discourse changed during the 1950s to a more or less open critique of administration realíties at the local leve!. This new rhetoric was flanked by fírst attempts in practical reform when district administrators tried to abolísh, at least partly, the repressive organisation of working conditions and native codex. Those reform measures that derived from a feelíng of indignation about the situation of the Black African populations, were continued under the auspices of the war of independence, as a strategy to wín over the native habítants support.